Penguatan Potensi Lokal Desa Grujugan: Sosialisasi dan Praktik Pembuatan Sabun Cuci Piring Homemade - Cinta Tarisa Arivia; Chika Uca Cystiana; Azza Lathifatul Ulum Zubaidah; Aufar Fadlul Hady (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The Community Service Program (KKN) with the theme of strengthening local potential towards prosperous independent villages was implemented in Grujugan Village, Pamekasan Regency, East Java. Based on field observations, the majority of the community are housewives who play an important role in managing household needs and have the potential to be economically empowered. This community service activity aimed to improve the knowledge and skills of PKK women through socialization and training in homemade dish soap production. The methods used were socialization, material presentation, and direct demonstration of dish soap production, involving 25 participants. The results of the activity showed that the demonstration process produced about 2 liters of liquid soap of good quality, as seen from its physical appearance, texture, and cleaning power. In addition, the packaged soap products were distributed to participants as a means of product introduction. This activity was able to increase participants' understanding, skills, and awareness of the potential of home-based businesses